War Pictures Cinema, History, and Violence in Britain, 1939-1945 - Puckett, Kent (World War II: The Global, Human, and Ethical Dimension, 2017)
In 'War Pictures', Puckett looks at how Britain imagined, saw, and sought to represent its war during wartime. How did the material and conceptual pressures of total war affect what it meant to see or to make art? How did culture and, in particular, cinema function as propaganda, as criticism, as a form of self-analysis, as a reflection on war and the kinds of violence it tends to unleash? How did British filmmakers, writers, critics, and politicians understand the nature and consequence of total war as it related to ideas about freedom and security, the idea of national character, and the daunting persistence of human violence? 'War Pictures' is also about violence, aesthetics, and conceptual difficulties of war in general; in other words, beginning with a close and critical analysis of a particular cultural scene, the author makes strong and important claims about where the historiography of war, the philosophy of violence, and aesthetics come importantly together.